MENELUSURI JEJAK DAN KIPRAH KIAI MOHAMMAD HASAN GENGGONG; DALAM MEMBANGUN KEPEMIMPINAN SPRITUAL-TRANSFORMATIF - Fauzi, Ahmad; Muali, Chusnul (JURNAL ISLAM NUSANTARA, 2018)
Pesantren and social value system is the result of constructing kiai's thoughts and social actions as an inseparable entity. This study aims to interpret the role and social action of kiai Moh Hasan, both as a fighter (al-haiah al-jihaadi li'izzi al-Islaami wal muslimin) in the community as well as guidance and guidance for the community (al-haiah al ta 'awuny wa al takafuly wal al ittijaahi) and teaching in educational institutions (al-haiah al ta'lim wa al-tarbiyah), significantly contributes greatly to the social realities of society in Indonesia. Portrait of central figure kiai Moh Hasan can not be separated from the depth of his field of Islamic science, simplicity, kezuhudan, struggle, sincerity and generosity. This view, not only recognized among the people around the boarding school, students and colleagues, but also spread in some areas in Indonesia. The fame of kiai Moh Hasan among scholars, habaib and society has many karamah and some other privileges, not even a few from the social recognition of kiai Moh Hasan Genggong, because the kiai are believed to have closeness with God, thus perceived as auliya'Allah. Thus the role and social actions of the kiai above, gave birth to the value system, so as to influence and move the social action of other individuals. The internalization of the aforementioned values becomes social capital in building a spiritual-based transformative leadership, as a strong leadership model and conducts various changes in the social field, by transforming the value of the ethical values.